A Clinical Program for Transgender and Gender-Diverse Neurodiverse/Autistic Adolescents Developed through Community-Based Participatory Design. Issue 6 (2nd November 2021) - Strang, John F.; Knauss, Megan; van der Miesen, Anna; McGuire, Jenifer K.; Kenworthy, Lauren; Caplan, Reid; Freeman, Andrew; Sadikova, Eleonora; Zaks, Zosia; Pervez, Noor; Balleur, Anouk; Rowlands, D. W.; et al.
ABSTRACT: Objective : A series of studies report elevated rates of autism and autistic characteristics among gender-diverse youth seeking gender services. Although youth with the co-occurrence present with complex care needs, existing studies have focused on co-occurrence rates. Further, clinical commentaries have emphasized provider-centered interpretations of clinical needs rather than key stakeholder-driven clinical approaches. This study aimed to employ community-based participatory research methodologies to develop a key stakeholder-driven clinical group program. Method : Autistic/neurodiverse gender-diverse (A/ND-GD) youth ( N = 31), parents of A/ND-GD youth ( N = 46), A/ND-GD self-advocates ( N = 10), and expert clinical providers ( N = 10) participated in a multi-stage community-based participatory procedure. Needs assessment data were collected repeatedly over time from A/ND-GD youth and their parents as the youth interacted with one another through ongoing clinical groups, the curriculum of which was developed progressively through the iterative needs assessments. Results : Separate adolescent and parent needs assessments revealed key priorities for youth (e.g., the importance of connecting with other A/ND-GD youth and the benefit of experiencing a range of gender-diverse role models to make gender exploration and/or gender affirmation more concrete) and parents (e.g., the need for A/ND-related supports for their children as well as provision of an A/ND-friendly environment that fosters exploration of a range of gender expressions/options). Integration and translation of youth and parent priorities resulted in 11 novel clinical techniques for this population. Conclusions : With generally high acceptability ratings for each component of the group program, this study presents a community-driven clinical model to support broad care needs and preferences of A/ND-GD adolescents.